2018
DOI: 10.1038/s41398-018-0318-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of convergent ion channel pathways in microglial phenotypes: a systematic review of the implications for neurological and psychiatric disorders

Abstract: Increases in the activated state of microglia, the main neuroimmune cells, are widely reported in the brains of patients with neurological and psychiatric disorders. Microglia transform from the resting to the activated state by sensing their environment, aided by a variety of ion channels. To examine the effect of ion channels on microglial phenotypes, we conducted a systematic review of immunohistochemical analyses of these neuroimmune cells in animal models following administration of ion channel antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Channelopathies are of particular interest in cardiology and neurology but are also notable in pain and emotional disorders. [21][22][23][24][25][26] Voltage-gated sodium channels are thought to be involved in general anesthesia. 27 Adverse effects of some psychotropic medications are best understood as ion channel dysfunction.…”
Section: Commentsandcontroversiesmentioning
confidence: 99%
“…Channelopathies are of particular interest in cardiology and neurology but are also notable in pain and emotional disorders. [21][22][23][24][25][26] Voltage-gated sodium channels are thought to be involved in general anesthesia. 27 Adverse effects of some psychotropic medications are best understood as ion channel dysfunction.…”
Section: Commentsandcontroversiesmentioning
confidence: 99%
“…Many studies have been conducted to understand the molecules responsible for microglial activation and the pathways that these molecules activate (Raivich et al, 1999;Hung et al, 2017;Xu et al, 2018). Microglia have been thought to play a triggering role in electrical changes caused by neuronal damage and ion changes around the damaged neurons in molecular activation in in vivo studies (Quagliato and Nardi, 2018), while some studies have indicated that activation occurs by low molecular weight active molecules (peptides, hormones, etc.) (Park and Chun, 2017;Bast et al, 2018).…”
Section: Molecules Triggering Microglial Activationmentioning
confidence: 99%
“…In response to various stresses, microglia show hypertrophic and/or elongated morphologies with hyper-ramified processes (intermediate states) and finally amoeboid shape indicating phagocytic and cytotoxic activity (activated states) [2]. Microglial activation is mediated by various receptors and ion channels (such as purinergic receptors, C-X3-C motif chemokine receptor, transient receptor potential channel (TRPC) and K + channels), which activate diverse signaling molecules including the nuclear factor of activated T-cells, nuclear factor-κB (NFκB), mitogen-activated protein kinases (MAPKs) and phosphatidylinositol-3-kinase (PI3K)/AKT [3]. This microglial activation seems to play an important role in epileptogenic processes.…”
Section: Introductionmentioning
confidence: 99%